Exploring EFL Students' Metacognitive Knowledge Based On Their Listening Abilities in Lubuklinggau - Fiani, Ani; Syafitri, Dewi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
Metacognition, as a 21st-century skill, is essential in language education. Students that have this competence are those who can manage or direct their own learning experience both within and without the classroom. Since the existing study found a positive linkage between the concept and success in language learning, particularly listening, it is critical to be conscious of metacognitive knowledge in listening comprehension. Thus, the current study aims to investigate the metacognitive knowledge of EFL undergraduate students in Lubuklinggau, South Sumatera, based on their listening abilities. This study divides metacognitive information into three categories: knowledge of self, learning techniques, and learning task needs.To elicit the research data, there were three types of data collection tools, namely questionnaire, test and semi-structured interview and this study used quantitative and qualitative methods based on a case study approach. The research findings indicated that students who have high listening abilities are better in metacognitive knowledge compared those who have middle and low listening abilities. Then, those students also were able to benefit effective learning strategies, particularly metacognitive strategies, in improving their listening abilities in and outside the classroom. Therefore, the students’ metacognitive knowledge has a potential role in helping them to become successful language learners. Keywords: Metacognitive knowledge; EFL listening abilities